TINGKAT BAHAYA EROSI DAN KEMAMPUAN LAHAN UNTUK MENENTUKAN ARAHAN PENGGUNAAN LAHAN DI SUB-DAS TINALAH - , RIEZHA RIZKY DANIAR ([Yogyakarta] : Universitas Gadjah Mada, 2013)
and make more critical lands Tinalah Sub Watershed has an area of 6969,29 ha and it is located at two districts which are Samigaluh and Kalibawang. Most of the area in Tinalah Sub Watershed has been used for rice field and farming. Improper land use can cause erosion . The study purposed to make level of Erosion Hazard assessment, reviewing Land Capability in Tinalah Sub Watershed area, and also to determine the instruction and management of land use areas in accordance with land capability. There are two steps to collect data during the research, collected ground characteristic data and land capability factors by observating the locations and also took secondary data. To calculate the value of erosion were calculated using USLE (Universal Soil Loss Equation) and then determined erosion risk level based on the value of erosion and effective depth of soil. Assessment of land capability class and land use instruction approach by matching the observed data with tables according to the USDA system. The result of this research indicated that most of Tinalah Sub-Watershed area erosion risk level has a value that is very heavy area broadly 4231.9 ha (61.59%). There are 6 classes of land capability in the Tinalah Sub-Watershed and the widest is land capability class VI area broadly 1511.39 ha (21.99%). Land use instruction of Tinalah Sub-Watershed area are as community forest area broadly 4444.318 ha (64.68%), protected forest area broadly 323.44 ha (4.7%)